The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s10554-006-9184-6
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of myocardial perfusion and rejection in cardiac transplant patients

Abstract: This study suggests that perfusion MR imaging can be used in assessing the cardiac transplant patient for rejection related microvascular changes. The high specificity and sensitivity recorded from the ROC curve illustrates the potential utility of this diagnostic test for future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In this study, stress MBF was significantly decreased in patients with later rejection (3.27±0.74 mL/min/g), compared with patients without later rejection (3.60±0.72 mL/min/g; P=0.067). The area under the receiver operating characteristic curve was 0.82, with a specificity and sensitivity of 75% and 81%, respectively [44].…”
Section: Clinical Application Of Absolute Mbf Quantificationmentioning
confidence: 96%
See 1 more Smart Citation
“…In this study, stress MBF was significantly decreased in patients with later rejection (3.27±0.74 mL/min/g), compared with patients without later rejection (3.60±0.72 mL/min/g; P=0.067). The area under the receiver operating characteristic curve was 0.82, with a specificity and sensitivity of 75% and 81%, respectively [44].…”
Section: Clinical Application Of Absolute Mbf Quantificationmentioning
confidence: 96%
“…Rivard et al [44] demonstrated that absolute MBF quantification by perfusion MRI could potentially be useful for assessing rejection-related microvascular changes in cardiac transplant patients. Acquiring tissue for histological analysis, which is a current gold standard to evaluate rejection, requires an invasive myocardial biopsy with its inherent risks.…”
Section: Clinical Application Of Absolute Mbf Quantificationmentioning
confidence: 99%
“…88,89 Novel methods such as nuclear perfusion and cardiac magnetic resonance imaging may have an evolving role, especially in detecting myocardial edema and increased LV mass. [90][91][92][93][94][95][96][97] One of the most promising cardiac magnetic resonance imaging modalities is T2 quantification. T2 relaxation time is the decay time constant of the magnetic signal after an excitatory pulse.…”
Section: Assessment Of Amr Imaging Modalitiesmentioning
confidence: 99%
“…IVUS and optical coherence tomography on the other hand were not used to evaluate the wall of coronary vessels, which may show increased intimal thickness despite normal appearance on coronary angiograms (25). Humoral rejection characterized by induced and complement-mediated activation of endothelial cells and macrophages, may also have a significant impact both on myocardial perfusion and on outcomes (26,27). In our study, however, the presence of antibodymediated rejection was not systematically evaluated, which is a limitation, particularly in light of its potential impact on microvascular function (28).…”
Section: Potential Pathophysiologic Mechanismsmentioning
confidence: 99%